THE EFFECT OF SERVICE QUALITY AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY PT. ASTRA INTERNATIONAL DAIHATSU SERANG - Surti Zahra; Sucihati (SEAN Institute, 2022)
In every business entity, especially in the field of services, it is essential to pay attention to the quality of service because it is directly related to customer satisfaction that the customer feels to create customer loyalty. This research aims to know the influence of service quality and customer satisfaction on customer loyalty at PT. Astra International Daihatsu Attack This type of research is quantitative descriptive research. The population of this study is car service customers at PT. Astra International Daihatsu Serang as many as 75 respondents. While the determination of samples using nonprobability sampling techniques with a saturated sample approach. The data used are primary data, obtained through the dissemination of questionnaires to a sample of 75 respondents. The analytical tools used are correlation, multiple linear regression, determination coefficient, and hypothesis test. The results of the first hypothesis test (H1) are known to be a significant value of 0.000 < 0.05 and a t-count value of 5,261 > t-table value 1.9935, so it can be concluded that H1 is accepted. The results of the second hypothesis test (H2) are known to be a significant value of 0.000 < 0.05 and a t-count value of 10,931 > a t-table value of 1.9935, so it can be concluded that H2 is accepted. The results of the third hypothesis test (H3) are known to be a significant value of 0.000 < 0.05 and an F-count value of 1413,177 > F-table 3.12, so it can be concluded that H3 is accepted. Moreover, the determination coefficient (R2) is 0.975 or 97.5%. Based on the hypothetical test results can be concluded that the quality of service affects customer loyalty, customer satisfaction affects customer loyalty, quality of service and customer satisfaction together affect customer loyalty